Penegakan Hukum Terhadap Perjudian Togel Online Pada Polres Maluku Tengah - Taufik Sabenjara Kalidupa; Sherly Adam; Judy Marria Saimima (Faculty of Law Universitas Pattimura, 2023)
ABSTRACK: This study aims to discuss Law Enforcement Against Online Togel Gambling at the Central Maluku Police and efforts to deal with online lottery gambling at the Central Maluku Police. The type of research used is empirical juridical research. Central Maluku Police research location. Population, sample and respondents Polres Investigators of Central Maluku Regency and 5 community members. Data sources are primary data and secondary data. Legal material collection techniques through interviews and documentation studies. Data processing techniques through editing and qualitative data analysis techniques. The results of this study indicate that the role of the Central Maluku Police in enforcing the law against online lottery gambling at the Central Maluku Police has been carried out in accordance with statutory provisions, but in carrying out law enforcement against online lottery gambling the role of the Police is still there are factors that influence law enforcement against online lottery gambling at the Central Maluku Police, including the legal factor itself or the law, factors of law enforcement officials, factors of facilities and infrastructure, community factors and servers placed in countries where gambling is legalized. Efforts to deal with online lottery gambling were carried out by the Central Maluku Police through preventive and repressive efforts. Preventive efforts include providing advice and counseling or outreach to schools and the community regarding online gambling and providing knowledge of the dangers and losses that can be obtained when carrying out online gambling. Repressive efforts include imposing sanctions on online tigel gambling actors by applying Article 303 and/or 303 bis of the Criminal Code and Article 27 paragraph (2) and Article 45 of the Electronic Information and Transaction Law.